Taman Mini Indonesia Indah: Education or Entertainment? - Wulandari, Anak Agung Ayu (Humaniora, 2013)
With combination of attractive appearance, taste, smell and sound, open air-museums can offer so many things to visitors; from educate to educate and entertain. Here, ?edutainment? concept starts to take place. The problem is there can be misconception between the creators and visitor?s perception. In this research, qualitative methodology, through  interviews to get information form creator?s perspective and visitor survey to get information form the visitors? perspectives were conducted with Taman Mini Indonesia Indah as the case study. The findings show that there is still misconception about education and entertainment perceptions in Taman Mini. Taman Mini has strong educational purposes, but because of ack of attractive educational programs, lack of information and interpretation and no encouragement to participate in the educational programmes, visitors considered their visits as recreational, rather than educational. In relation with postmodern phenomenon, Taman Mini can be considered as postmodern and adopting ?edutainment? concept, but this concept has became blur and vague, thus Taman Mini now only famous as a recreation venue.